Review on Local News’s Transition Towards Digital Media - Bhavik Mittal; Hitharth Jain; Apra Sharma; Himanshu; Aashika; Anjali Singh (International Journal of Information Security Engineering, 2024)
The development of a contemporary news web application is centered around delivering a captivating user experience replete with advanced functionalities for consuming news. Tailored for daily newspaper readers, the application offers a seamless blend of reading and auditory experiences, allowing users to listen to news articles. Its dynamic homepage algorithmically curates content based on users' historical searches, presenting them with articles that align with their interests. A real-time comment section fosters active engagement, nurturing discussions, and feedback from the community. Furthermore, an admin-user portal facilitates seamless CRUD (create, read, update, delete) operations and user management, enhancing the overall administrative experience. Crafted using a robust technology stack comprising HTML, CSS, JavaScript, and React, the application boasts full responsiveness and cross-device accessibility, ensuring a consistent user experience regardless of the platform. Rigorous testing methodologies and benchmarking have been employed to ensure optimal performance, guaranteeing minimal latency even during peak user traffic periods. To safeguard user data and prevent potential cyber-attacks, the application incorporates robust security measures, including encryption, authentication mechanisms, and access controls. Looking ahead, the application is poised for further evolution and enhancement through ongoing development and research initiatives. In upcoming initiatives, the focus lies on discovering fresh avenues to enhance its functionalities and elevate user satisfaction. The development team is also committed to staying abreast of emerging technologies and trends to maintain the application's relevance in the rapidly evolving digital landscape.
Keywords: Application; CSS; HTML; JavaScript; digital media